Dari Sekolah ke Dunia Kerja: Profesionalisme, Etika dan Keselamatan - Rahutama, Ilham; Sagaf, Muhammad; Marlyana, Novi; Prianjani, Dana; Mohammad, Gunawan (Universitas Dinamika, 2026)
The Vocational High School students often face challenges in transitioning from the academic environment to the workforce, particularly in non technical skills. To address the crucial need for soft skills development, a One Day Workshop was implemented focused on professionalism, ethics and safety culture for the students. The workshop entitled “From School to the Workplace: Professionalism, Ethics and Safety,” was held at SMKN 1 Muara Teweh and employed interactive methods, including direct instruction on growth mindset and personal branding, case study discussions and group brainstorming sessions. A Pre-Test and Post-Test were conducted to measure changes in knowledge and perceptions. Key findings revealed a 13% reduction in fixed mindset misconceptions, a 10% increase in the recognition of work integrity and 10% improvement in understanding the purpose of Occupational Safety and Health (OSH). Perception of failure as a learning opportunity increased by 24%, belief in the ability to develop skills improved by 14% and a sense of responsibility for safety rose by 10%. Participant feedback on the workshop’s quality was positive in all categories, with mean rating scored 4.6 out of 5 point scale. This workshop proved to be an effective and engaging method for enhancing vocational students’ conceptual understanding of soft skills. The outcomes highlight the necessity of embedding such targeted and interactive refreshment or training sessions within the vocational education curriculum.